Reporting Technical Information; Designlng Technical Reports; IBM Dictionary of Computing - Robert G. Hays; Carol Sanders Reiner (Journal of Applied Communications, 1992)
Book reviews of Reporting Technical Information, by Kenneth W. Houp and Thomas E. Pearsall; and Designlng Technical Reports, by J.C Mathes and Dwight W. Stevenson; IBM Dictionary of Computing (Ninth Edition), International Business Machines Corporation.